International financial reporting : - Roberts, Clare (Prentice Hall, 2005)
Fully updated to reflect the ongoing changes in international accounting standards, International Financial Reporting contrasts the processes of convergence on global harmonisation with the continuing causes of national diversity in accounting and accountability. It analyses the work of the International Accounting Standards Board in setting internationally applied standards (IFRS) of measurement and disclosure.